PENINGKATAN PENGETAHUAN DOSEN TENTANG PEMBUATAN RENCANA PEMBELAJARAN DI JURUSAN KEPERAWATAN POLITEKNIK KESEHATAN KEMENKES JAYAPURA - , NURMAH RACHMAN; , Prof.dr.Harsono, Sp.S (K), ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. A lesson plan is a plan that describes the procedures and organization of learning to achieve a competency. Lesson plan is content and process standards in the national education standards of The government regulation No.19 Year 2005, as an important component in learning. Thus, it takes a workshop to increase knowledge, understanding, skills and applications of making lesson plans, learning method based on problems with the constructivist approach in the implementation of student centered learning. This is a lecturerâs professional competency. Objective. This study was conducted to identify a lecturerâs knowledge and skills, ability and motivation to make design of lesson plans in Department of Nursing at the Jayapura Health Polytechnic in 2011 and to provide input for policy makers in making innovations in education, especially the development of the semester learning plans, the selection method of learning, and effective and efficient assessment methods. Research Methodology. This was a descriptive qualitative study with an action research approach that consisted of two cycles with the steps as follows: the first cycle which comprised: step 1) Identifying the study topic in which the lecturers made lesson plans, then followed by the execution, observation and reflections, without the intervention to the study subjects and step 2) Evaluating the learning process and determining the problem